(untitled) (Nepalese Journal of Management Research, 2024)
Relationship marketing is the efforts done by insurance companies making long lasting and profitable relationship with these customers. The main objective of this research is to analysis impact of relationship marketing to make customer’s brand loyal towards insurance companies of Chitwan. In this regards, results are found out the personalized service makes customers’ brand loyal towards insurance company of Chitwan. Thus relationship marketing ensures to make brand loyal towards insurance companies.